2004
DOI: 10.5301/jbm.2008.1233
|View full text |Cite
|
Sign up to set email alerts
|

Serum HER-2 extracellular domain: Relationship with clinicobiological presentation and prognostic value before and after primary treatment in 701 breast cancer patients

Abstract: sHER-2 elevation in early breast cancer correlates with the principal criteria of tumor aggressiveness, thus permitting selection of patients with a high risk of visceral metastases and contralateral breast tumors. Post-treatment sHER-2 is an independent prognostic factor enabling to identify patients likely to benefit from aggressive adjuvant treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
2
6
0
8
Order By: Relevance
“…The results of our prospective study are in agreement with two retrospective studies [28,24] that showed a shorter DFS in patients with elevated serum HER2 ECD levels. The adverse prognostic value of elevated HER2 ECD levels in early breast cancer could reflect the presence of micrometastases or high HER2 cleavage and shedding with the production of truncated cell-associated fragments that contain the signaling kinase domain activated in absence of the ECD [29].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of our prospective study are in agreement with two retrospective studies [28,24] that showed a shorter DFS in patients with elevated serum HER2 ECD levels. The adverse prognostic value of elevated HER2 ECD levels in early breast cancer could reflect the presence of micrometastases or high HER2 cleavage and shedding with the production of truncated cell-associated fragments that contain the signaling kinase domain activated in absence of the ECD [29].…”
Section: Discussionsupporting
confidence: 82%
“…The percentage of elevated serum levels of HER2 ECD are extremely variable in early breast cancer patients at the time of diagnosis. In our study, high HER2 ECD levels were observed in 9.0% of early breast cancer patients, similar to the results reported by other authors [22][23][24].…”
Section: Discussionsupporting
confidence: 81%
“…Studies have shown that serum HER2 levels, prior to treatment, positively correlate with tumor size, number of positive lymph nodes and histological scores [25]. In fact, serum HER2 levels were a better indicator for stage IV breast cancer than were IHC scores [26].…”
Section: Her2mentioning
confidence: 99%
“…In fact, serum HER2 levels were a better indicator for stage IV breast cancer than were IHC scores [26]. Serum HER2 levels were also an effective prognostic indicator for metastasis-free and disease-specific survival after treatment cessation [25]. FACTT was used to detect and quantify HER2 in both rodent and human blood [12].…”
Section: Her2mentioning
confidence: 99%
“…En revanche, une valeur sérique normale ne peut pas être corrélée à une absence de surexpression de c-erb B2 par la tumeur. L'élévation de l'ECD dans les cancers précoces témoigne de l'agressivité de la tumeur et paraît associée à une augmentation du risque de métastases viscé-rales et de cancers mammaires controlatéraux [47]. Une augmentation des valeurs sériques d'ECD a un impact péjo-ratif sur la survie globale et sans récidive.…”
Section: C-erb B2unclassified